Unleashing Gender Transformative Change through Household Level Gender Exercise - Haque, S.M. Faridul (International Fertilizer Development Center, 2023)
Social norms, values, and practices at the household level in most cases create barriers for women to be involved in income-generating activities. The aquaculture sector is one of the examples of such a field where women’s limited participation is determined by a set of negative perceptions and discriminatory practices. However, household-level gender exercise could be an effective tool to break these barriers due to its participatory and bottom-up nature. This paper focuses on the effectiveness of household-level gender exercise as a tool of a gender-transformative approach. It examines the efficiency of household-level gender exercise to enable people to identify and adopt alternatives to the existing gender-biased practices within the family. A qualitative study was conducted in July 2022 with the members of 15 households where 20 men and 20 women were respondents in the northwestern part of Bangladesh. The findings show that household-level gender exercise creates an enabling environment for both men and women to be agents of breaking the gender biases by challenging existing harmful norms. This article illustrates the importance of householdlevel gender exercise as a gender-transformative tool to ensure women’s participation and benefit from the aquaculture sector.